Temperature dependence of space-charge limited current in thin films of CdS - Srivastava S.K.; Bhattacharyya R. (My University, 2025)
An experimental investigation is made of the temperature dependence of space-charge limited (SOL) current in vapour-doposited thin films of cadmium sulphide. It is observed that for a fixed voltage the SCL current attains a maximum value at a particular temperature, corresponding to the depth of the shallow traps present in the film. An expression for the temperature dependence of the SCL current in presence of traps is derived assuming a T-n dependence for the mobility. Full agreement is found between experimental and theoretical results for n = l.8. © 1969, Walter de Gruyter. All rights reserved.